THE SIGNIFICANCE OF PEDAGOGICAL TECHNOLOGIES AND FOREIGN EXPERIENCES IN FOREIGN EDUCATION AND THE PRINCIPLES OF ITS IMPLEMENTATION IN UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
This article considers the following goals: analysis of foreign experience in training competitive personnel, identification of problems in training competitive specialists in higher educational institutions of the Republic and search for their solutions, as well as determination of tasks to be performed in personnel training.